Model Perlindungan Hukum oleh Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) terhadap Perempuan dan Anak Korban Tindak Kekerasan di Sumatera Barat - Efren Nova (Fakultas Hukum Universitas Riau, 2022)
Based on data from the West Sumatran Women's Conscience NGO, the number of violence against women and children in West Sumatra in the 4 (four) years is still very high. The research method used in this research is sociological juridical. Based on the results of research at the Integrated Service Center for the Empowerment of Women and Children at 5 (Five) Regencies/Cities in West Sumatra: the model of protection by P2TP2A for women and children victims of violence is through prevention efforts carried out through socializing the existence of P2TP2A, handling complaints services, rehabilitation services health services, social rehabilitation services, legal aid services and information data administration services, recovery is carried out through training training so that victims can become independent and social rehabilitation so that victims can socialize again into the community.